Trans Laws and Constitutional Rulings in Belgium: The Ambiguous Relations between Sex and Gender - Meier, Petra (2020)
In this article we reflect upon the evolution from the Belgian trans law of 2007 to those of 2017 and beyond, giving adult citizens the possibility to have their self-determined gender legally recognised. The 2019 ruling of the Belgian Constitutional Court, condemning the Belgian State for being discriminatory against gender fluid and gender non-binary persons regarding their legal gender recognition, requires the Belgian government to either add a third legal option or to abolish gender registration altogether. We analyse the definitions of sex and gender that underlie the two trans laws of 2007 and 2017 and the Constitutional Court ruling of 2019 and then confront them with the experiences of trans people based on a national transgender survey (Motmans, Wyverkens, & Defreyne, 2017). The confrontation between legal texts and lived experiences clearly shows the promises and pitfalls states face when striving for gender recognition procedures.